Sosialisasi Penyelesaian Sengketa Tanah Melalui Litigasi dan Non Litigasi di Desa Patila - Andi Wahyuddin Nur; Dewi Wahyuni Mustafa; M. Asraf Fradama; Asriani Said; Rina Febrianti; Andi Nur Halisa; Rismawati; Andi Muh. Iswan; Erwin (YP-SDI Lamaddukelleng, 2024)
The occurrence of land disputes can be attributed to the fact that land occupies a pivotal position in this regard, whereby it can serve to demonstrate the independence and sovereignty of its owner. It is not always necessary to resolve disputes through the judicial process. At the present time, a new form of dispute resolution has emerged, namely Alternative Dispute Resolution (ADR). One such method is mediation, whereby the mediator does not take a partisan stance on the issues under discussion. Mediation encourages the open communication of problems and interests between the parties involved. It is therefore necessary to socialise the resolution of land disputes in Patila Village through both litigation and non-litigation. This should encourage the parties to realise that disputes are not fights that must be won but resolved. The aim is to help the parties reach common ground and to facilitate the procedures for resolving land disputes through mediation. This will involve a complaint by the parties to the dispute to the Land Office and a process of reviewing, final negotiation and an agreement set out in a written agreement. However, if the parties are unable to reach an agreement, they have the right to submit the dispute to the court.